نموذج مقترح لمحاسبة الموارد البشرية وفق النظام المحاسبي المالي - سعدي, عبد الحق (جامعة الوادي University of Eloued, 2019)
تهدف هذه الدراسة إلى وضع نموذج مقترح لمحاسبة الموارد البشرية وفق النظام المحاسبي المالي، وذلك لاعتبار موضوع محاسبة الموارد البشرية من أهم المواضع الحديثة في المجال المحاسبي نظرا إلى مدى لأهمية العنصر البشري داخل المؤسسات بمختلف أشكالها، حيث تم ابزرا أهمية وأهداف محاسبة الموارد البشرية، كما تم أيضا توضيح الفروض التي ترتكز عليها وأهم الطرق لقياس قيمة المورد البشري، ومن خلال كل هذا تم اقتراح نموذج للمعالجة المحاسبية للمورد البشري وفق النظام المحاسبي المالي. this study aims to develop a proposed model for accounting human resources in accordance with the financial accounting system, in order to consider the issue of human resources accounting as one of the most important modern positions in the field of accounting because of the extent of the importance of the human element within institutions in all its forms. Also clarifying the hypotheses that underpin the most important methods to measure the value of the human resource, and through all this was proposed a model for accounting treatment of the human resource in accordance with the financial accounting system
Proposed model for accounting of human resources in accordance with the financial accounting system
مقال
Keywords: موارد البشرية، محاسبة الموارد البشرية، تكلفة التاريخية، معالجة المحاسبة للمورد البشري.; Human resources. Human resources accounting. Historical cost. Accounting treatment of the human resource.